แรงจูงใจในการเล่นกีฬาบาสเกตบอล ของนักกีฬาบาสเกตบอล ในการแข่งขันกีฬามหาวิทยาลัยแห่งประเทศไทย ครั้งที่ 40 - Prasarntree, Phattaradanai (Academic Journal of Thailand National Sports University, 2013)
This study was intended to find and compare motivation for selecting to play basketball of basketball players participating in the 40th Thailand University games 2013. The subjects of 240, 144 male players and 96 female players, were simple randomly sampled from the basketball players who participated in 40th Thailand University games 2013, The data were collected by the writer's constructed questionnaire (r = .95) in 4 areas of motivations: Preference, Interest and Skills, 2. Attitude toward Self and Concerning People, 3. Benefits , Opportunities and 4. Honor / Fame After the data were treated for percentage, mean, standard deviation, t-testing for mean difference, One-Way ANOVA and Schaffe's Pairing Method, it was found as follows: As a whole, the motivations in all areas were at a high level 2. Compared motivations to play basketball. 2.1 When compare the motivations between male subjects and female subjects, there were no significant differences of means. 2.2 When compare among the experience of basketball players, there were no significant differences between motivations.